Building Fengshui IOS app with RubyMotion - Chan, Dennis Joon Ming (2018)
This is a free iOS application which is written based on the book 'A Master Course in FengShui'. All Fengs Shui rules are being translated into ruby language and the application is written using RubyMotion. Users are now able to access the Feng Shui condition of a property using this app instead of employing Feng Shui practitioners. This app presents the result in a layman term so as to make status of the house easily understandable at the common crowd. Feng Shui APP is written in RubyMotion language. RubyMotion is a simple language for writing mobile apps built on top of ruby. It is similar to Objective-C. However, RubyMotion is more flexible and applicable than objective-c.